PERANCANGAN STRATEGI PEMASARAN PADA USAHA U ONE PLASTIC DENGAN IMPLEMENTASI MATRIKS SWOT DAN QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) - Puja Ahmad Furgani (2023)
U One Plastic is a business located in a shop house (shophouse) that has only been running for about one and a half years. U One Plastic operates in a two-story shophouse. The problem faced arises because the net profit from July to December 2022 has decreased. The purpose of this study was conducted to identify and analyze the company's internal and external environmental factors that affect marketing strategies and determine the best alternative strategies that can be applied to increase sales at U One Plastic. Determination of the position of the IE matrix is based on the results of the total score of the IFA matrix which is weighted on the X axis and the total score of the EFA matrix on the Y axis. The total value of the IFA matrix is 2.74138 and the value of the EFA matrix is 3.1074 so that the position of U One Plastic is obtained in quadrant 2, where this position is Grow & Build. Based on the results of the SWOT matrix, 12 alternative strategies are obtained and then prioritized from first to twelfth using QSPM. The first priority of alternative strategies obtained is " Find out which products are rarely purchased by consumers and then stop buying these products from suppliers and focus on products that are frequently purchased ".